The Role of Islamic Education in Building Digital Wellbeing and Social Media Ethics among Muslim Youth - Abror, M.Qusyairi; Noviani, Dwi (Westscience Press, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) in fostering digital wellbeing and social media ethics among Muslim adolescents. In the digital era, social media has become the primary space for youth expression and interaction, yet it also poses challenges such as moral degradation, digital addiction, and the spread of misinformation. Using a qualitative-descriptive approach, this research explores how Islamic values ​​are integrated into PAI learning to cultivate a balance between technological competence and spiritual awareness. The findings indicate that PAI plays a strategic role as an instrument for shaping Islamic digital character through the internalization of values ​​such as amanah (responsibility), tawazun (balance), sidq (honesty), and ihsan (excellence). PAI teachers act as moral exemplars in the digital realm, instilling politeness, responsibility, and communication ethics based on the principle of qaulan ma'rufan (kind speech). Project-based and reflective learning strategies are effective in enhancing students' ethical literacy and social empathy. In conclusion, PAI not only develops religious knowledge but also moral and spiritual awareness, guiding students to use technology wisely, productively, and ethically thus realizing digital wellbeing grounded in Islamic values ​​that embody rahmatan lil 'alamin (mercy to all creation).